2019
DOI: 10.1073/pnas.1908228116
|View full text |Cite
|
Sign up to set email alerts
|

Cell phenotypic plasticity requires autophagic flux driven by YAP/TAZ mechanotransduction

Abstract: Autophagy, besides ensuring energy metabolism and organelle renewal, is crucial for the biology of adult normal and cancer stem cells. However, it remains incompletely understood how autophagy connects to stemness factors and the nature of the microenvironmental signals that pattern autophagy in different cell types. Here we advance in these directions by reporting that YAP/TAZ transcriptionally control autophagy, being critical for autophagosomal degradation into autolysosomes. YAP/TAZ are downstream effector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
92
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(113 citation statements)
references
References 36 publications
14
92
3
Order By: Relevance
“…Confirming these observations, cell line experiments revealed that sphere-forming stem cell-like PDAC cells have higher levels of the autophagy marker LC3-II compared to other cells [28]. Another link between autophagy and PDAC cancer stem cells is YAP/TAZ-signaling, shown to be required for cell dedifferentiation and the acquisition of self-renewing properties, i.e., stem cell formation [29]. YAP/TAZ has also been shown to be a positive autophagy regulator [30], and promotes autophagic flux by increasing Armus expression, a RAB7-GAP required for autophagosome turnover [29].…”
Section: Conflicting Roles Of Autophagy In Pdacmentioning
confidence: 68%
See 1 more Smart Citation
“…Confirming these observations, cell line experiments revealed that sphere-forming stem cell-like PDAC cells have higher levels of the autophagy marker LC3-II compared to other cells [28]. Another link between autophagy and PDAC cancer stem cells is YAP/TAZ-signaling, shown to be required for cell dedifferentiation and the acquisition of self-renewing properties, i.e., stem cell formation [29]. YAP/TAZ has also been shown to be a positive autophagy regulator [30], and promotes autophagic flux by increasing Armus expression, a RAB7-GAP required for autophagosome turnover [29].…”
Section: Conflicting Roles Of Autophagy In Pdacmentioning
confidence: 68%
“…Another link between autophagy and PDAC cancer stem cells is YAP/TAZ-signaling, shown to be required for cell dedifferentiation and the acquisition of self-renewing properties, i.e., stem cell formation [29]. YAP/TAZ has also been shown to be a positive autophagy regulator [30], and promotes autophagic flux by increasing Armus expression, a RAB7-GAP required for autophagosome turnover [29]. The role of autophagy in PDAC survival is not limited to tumor cells alone, but extends to the tumor microenvironment.…”
Section: Conflicting Roles Of Autophagy In Pdacmentioning
confidence: 99%
“…The ECM and cytoskeletal tension also profoundly impact on autophagic flux by YAP/TAZ directly promoting the expression of the GTPase-activating protein Armus. In normal and in tumor cells, YAP/TAZ-mediated autophagy in response to physical cues is responsible for dedifferentiation and the acquisition of self-renewing properties [92].…”
Section: Yap and Taz As Relays Of Mechanosensorsmentioning
confidence: 99%
“…It has been reported that YAP-/TAZ-regulated autophagy is essential in normal cells and in tumor cells [ 27 ]; however, the effect of YAP/TAZ on autophagy in RA-FLS has not been elucidated. In order to define the relationship between YAP/TAZ and autophagy in RA-FLS, we first checked for the effect of knockdown of YAP/TAZ on the expression of autophagy-related genes by RT-qPCR and western blotting assays.…”
Section: Resultsmentioning
confidence: 99%